The influence of distribution of beta-casein genotypes in two generations on milk productivity of Kholmogory cattle - Natalya A. Khudyakova; Irina S. Kozhevnikova; Marina A. Kudrina (RUDN Journal of Agronomy and Animal Industries)
The relevance of the study lies in the possibility of purposeful formation of ahighly productive dairy herd of cattle with the most desirable gene combinations based on the identified patterns of genotype inheritance. The aim of the study was to determine patterns of inheritance of desired genotype in daughter offspring from various genotypes of their mothers and compare them with indicators of milk productivity. The study was conducted on two generations of cattle of Kholmogorsky breed (cows and their offspring) on the basis of ʺAgrofirma Kholmogorskayaʺ and ʺKholmogorsky plemzavodʺ. Determination of beta-casein gene polymorphism in Kholmogorsky cows was carried out by Allele-specific polymerase chain reaction method. There was apredominance of heterozygous beta-casein genotype in two generations, which was 58.5 and 60.0% in mother cows and 49.1 and 48.0% in daughter offspring. In both herds, the dominance of A1 allele was observed, which, accordingly, affects the inheritance of A1 allelic variants of genotypes, but A1A2 genotype was more common. In order to determine the most promising genotype for further breeding work, an assessment of milk productivity was carried out in terms of milk yield, fat and protein in milk for 305 days of the first lactation. Cows with A1A2 genotype were mainly characterized by higher milk yield. In the studied herds, the dominance of A1 allele and the predominance of cows with heterozygous A1A2 genotype were observed. On average, in farms for 305 days of the first lactation, cows carrying genotypes with A2 allele variant (A1A2 and A2A2) had the highest indicators for qualitative and quantitative composition of milk. Thus, in order to produce high-quality dairy products and effectively conduct breeding work on farms, it is necessary to increase the number of animals carrying A2A2 genotype.